Correlating the Optical Coherence Tomography Patterns and Biomarkers of Diabetic Macular Edema with Hemoglobin Level in Diabetic Kidney Disease - Gopalakrishnan N; Nagaraju SP; George NM; Bhandary SV; Kamath YS; Shetty SS; Nair SS; Kuzhuppilly NI; S S (Clinical Ophthalmology)
Nikhil Gopalakrishnan,1 Shankar Prasad Nagaraju,2 Neenu Mariam George,3 Sulatha V Bhandary,4 Yogish S Kamath,4 Sushan Shankar Shetty,4 Soumya S Nair,4 Neetha IR Kuzhuppilly,4 Shailaja S4 1Department of Retina, Narayana Nethralaya, Bangalore, Karnataka, India; 2Department of Nephrology, Kasturba Medical College Manipal, Manipal Academy of Higher Education, Manipal, Udupi, Karnataka, India; 3Aravind Eye Hospital, Coimbatore, Tamil Nadu, India; 4Department of Ophthalmology, Kasturba Medical College Manipal, Manipal Academy of Higher Education, Manipal, Udupi, Karnataka, IndiaCorrespondence: Shailaja S; Sushan Shankar Shetty, Department of Ophthalmology, Kasturba Medical College Manipal, Manipal Academy of Higher Education, Manipal, Udupi, Karnataka, 576104, India, Tel +91 9686125861, Fax +91-820-2571934, Email shailaja.s@manipal.edu; sushan.shetty@manipal.eduPurpose: To correlate the optical coherence tomography (OCT) based morphological patterns of diabetic macular edema (DME) and prognostic biomarkers with severity of anaemia in patients with diabetic kidney disease (DKD).Patients and Methods: Single centre, observational cross sectional study of 42 eyes of 42 patients with DME and DKD. Eyes were divided into 2 groups: Group A (Haemoglobin level above 10 g% and group B with haemoglobin less than 10 g%). The OCT pattern and biomarkers were compared between the two groups.Results: Mean age of the patients was 56.9 ± 8.1 (range 42– 79). Out of 42 participants, 22 patients had hemoglobin level more than 10g%(group A) while 20 patients had hemoglobin less than 10g%(Group B). The most common morphological pattern seen was combination of cystoid macular edema (CME) with diffuse retinal thickening (DRT) in both groups. Disruption of the external limiting membrane (ELM) and ellipsoid zone (EZ) was found to be associated with lower hemoglobin levels (p= 0.0155 and p= 0.0154 respectively). None of the other OCT biomarkers showed correlation with hemoglobin levels.Conclusion: CME with DRT is the most common morphological pattern of macular edema seen in DKD patients with anemia. ELM-EZ disruption can be considered as important biomarker of anaemia in patients with DKD.Keywords: anemia, central foveal thickness, external limiting membrane, cystoid macular edema, ellipsoid zone